Servants to the hospital and the state: nurses in Plymouth and Haslar Naval Hospitals, 1775–1815. (3rd July 2018) - Spinney, Erin
ABSTRACT: Historians have typically viewed the construction of naval hospitals in the mid-eighteenth century as, variously, the British imperial state's response to a broken system of contract care, a training ground for medical officers, a controlled and regimented space for healing, and a representation of the interests of the state through the quick return of sailors to ships. Yet, contemporaries conceived of the hospitals in household terms. Nurses, washerwomen, and labourers, were 'servants' of the hospital and often lived on the premises. Hospital agents kept a 'household book', composed of tradesmen's bills, disbursements, and ward books that detailed issues of coals, beer, and wine to the various wards. Adopting a household model facilitates envisioning the hospitals as dynamic systems that responded to internal and external forces. Pay list prosopography demonstrates how the number of nurses responded to epidemics and battle casualties. This analytical framework illuminates the stability of the core nursing staff further reinforcing the household dynamic.